PENGARUH LUAS LAHAN, PRODUKSI, HARGA INTERNASIONAL DAN KURS DOLLAR AMERIKA TERHADAP EKSPOR KAKAO INDONESIA - Sipayung, Eldeardo; Sitepu, Indrawaty; Nainggolan, Medi Lilis Wenny (Universitas Methodist Indonesia, 2023)
This study aims to determine whether there is a significant impact of the variable land area, sproduction, international prices, the dollar exchange rate on cocoa export volume simultaneously and partially. For this study the data collection used was secondary data, in which secondary data was obtained through the central statistics agency, ICCO and BI by first carrying out a classical test on each data obtained. The data analysis method was used to calculate all the data that had been obtained using emultiple linear regression analysis with the help of SPSS version 25. The results of this study are that simultaneously land area,lproduction, international prices, cocoa kdollarsvexchange have a significant effect on Indonesia's cocoa export volume. Partially, land area, fproduction, and fthe US dollar exchanges ratedhave a dsignificant effect on Indonesia's cocoa export volume. Meanwhile, partially international prices have no significant effect on Indonesia's cocoa export volume.